2010
DOI: 10.1007/978-3-642-13244-5_22
|View full text |Cite
|
Sign up to set email alerts
|

A Field Study on the Barriers in the Assimilation of Open Source Server Software

Abstract: Abstract. An increasing number of academic studies have been devoted to the organizational adoption of open source software (OSS). Most studies have either focused on determining which reasons influence the adoption of OSS, or which barriers prevent the adoption of OSS. To our knowledge, no prior study has been conducted to determine which barriers exist to the further adoption of OSS in organizations. Studies addressing this issue could provide more insight into whether organizations are effectively able to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…So, it is really worth it". The finding of the study is in line with the previous studies which indicated that an increase in reliability of OSS would enhance the adoption rate among users [14]. Consequently, the technology context attribute Relative Advantage was seen in terms of Reliability, and played an important role in OSS adoption.…”
Section: Enablers Of Oss Adoptionsupporting
confidence: 88%
See 2 more Smart Citations
“…So, it is really worth it". The finding of the study is in line with the previous studies which indicated that an increase in reliability of OSS would enhance the adoption rate among users [14]. Consequently, the technology context attribute Relative Advantage was seen in terms of Reliability, and played an important role in OSS adoption.…”
Section: Enablers Of Oss Adoptionsupporting
confidence: 88%
“…Reliability: Studies [14] indicated that increase in reliability of the OSS would enhance the adoption rate among users. The study by Dedrick and West [15] claims that even in larger organizations, reliability played a significant role.…”
Section: Factors Hypothesized To Influence Oss Adoptionmentioning
confidence: 99%
See 1 more Smart Citation